Community Empowerment In Gedangan Ngawi Village In Improving Health, Education And Economic Aspects - Desi Dwi Maheningsih; Abid Nurhuda (Indonesian Journal of Advanced Social Works, 2023)
The existence of the corona virus in people's lives so that it has such a big impact in Indonesia, especially in the aspects of health, education, and the economy. These three aspects are very vulnerable for the community to experience various obstacles and constraints that need to be improved. So the purpose of this research is to describe Community Empowerment in Gedangan Ngawi Hamlet in Improving Health, Education and Economic Aspects.The method used isqualitative descriptive, with interview, observation and documentation techniques. The results showed that community empowerment in Gedangan Ngawi hamlet in improving health, education and economic aspects included the active participation of children in learning activities tutoring and in the Al-Qur'an Education Park (TPA), the people of Gedangan hamlet began to open businesses from home. , the adherence of the people of Gedangan Hamlet to health protocols and the healthier condition of the community from illness.